EFFECT OF PROGRAMMED INSTRUCTION ON ACHIEVEMENT OF SECONDARY SCHOOL CHILDREN IN LIFE SCIENCE - Mohanty, Kundalini (SCHOOL SCIENCE, 2010)
Science and Technology have created a phenomenal impact in shaping the lifestyle of human beings all over the world. Now-a-days all disciplines are becoming more scientific. Our method of observation becomes more symbolic, graphical and linguistic models in every discipline. Speaking on our dependence on science.